Su alcune implicazioni filosofico-giuridiche della crisi provocata dal Covid-19 (Società e diritti, 2021)
AbstractThe crisis caused by Covid 19 has brought to the surface certain aspects of the economic and social inequalities produced by neoliberal globalisation, which make it increasingly difficult to build common spaces potentially open to the active participation of all citizens. In this way, a veritable "imaginary of exclusion" is affirmed, leading to a drastic reduction, in terms of concrete effectiveness, of the inclusive and emancipatory capacity of law. As a result, the function of "mediation" - understood as a process of construction and integration of citizenship - which in constitutional democracies the law has been able to assume as a social practice (not neutral but) oriented towards the implementation of fundamental rights, is no longer there.